(3MbGFb CSQGQ GdWHs - (3eSYhO Hf eMeO GdSLRj GdWHjHs
(3ChdgG (B:s
(3GdMeO ddg Ydi EjGOjg GdeJhGJQI hUfGFYI hHYO aEf aLeYJ gPG GdcJGH HGSeg hQJHJg QSeg hSejJg MbGFb CSQGQ GdWH s
(3BNQgG (B:s
(3GdQcHI KeGfjI YVdI GdbOe SHY YVdGJ GdCUGHY EKfGf hYTQhf YVdI Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B672s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs